Effect of Nitrogen on Growth, Yield and Quality of Beet root (Beta vulgaris subsp. Vulgaris L.) - Choudhary, Anita; Bairwa, L. N.; Choudhary, Rajesh; Choudhary, Ashok; Sharma, Yogesh Kumar (Current Horticulture, 2025)
A field experiment was conducted to study the effect of nitrogen on growth and yield of beet root (Beta vulgaris) during rabi season 2020-21 at Horticulture Farm, S.K.N. College of Agriculture, Jobner (Rajasthan). The experiment consisted of Twelve treatment combinations including four nitrogen levels (control, 30 kg N/ha, 60 kg N/ha and 90 kg N/ha) and three treatments of plant geometry (15 cm x 10 cm, 30 cm x 10 cm and 45 cm x 10 cm) were under taken in a factorial randomized block design with three replications. The application of 60 kg nitrogen was significantly. However, 60 kg nitrogen significantly increased plant height (42.47 cm), No. of leave plant (16.53 cm leaf area, (cm2) (1.05), chlorophyll content (mg/100 g) (5.14g), yield per plot (26.16 kg), yield (261.60 q), net return (Rs/ha) 174 601.21/ha and B: C ratio (2.01).